2008
DOI: 10.1007/s00421-008-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased plasma osmolality on cold-induced thirst attenuation

Abstract: The eVects of elevating plasma osmolality (P osm ) on thirst ratings was studied in eight dehydrated males during exposure to 4°C. On two occasions, subjects were dehydrated (DH; 3-4% body mass) via 90 min exercise-heat exposure and overnight Xuid restriction (day 1). On a third occasion, subjects were exposed to heat but were given Xuid (EU). On day 2, subjects consumed NaCl (NaCl; 0.1 g NaCl kg ¡1 body mass in 500 ml H 2 O; DH only) or Placebo (P; 500 ml H 2 O; DH and EU). Subjects stood for 30 min at 24°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Above this threshold value, it has been reported that the first sensation of thirst occurs, ultimately resulting in a desire to drink. In the cold it has also been suggested that there is a blunted thirst response which may affect water intake volumes (Kenefick et al, 2008). Following 30-min exposure to the cold, Kenefick and colleagues reported that the sensation of thirst was attenuated to a serum osmolality threshold of approximately 304 mOsmol·kg -1 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Above this threshold value, it has been reported that the first sensation of thirst occurs, ultimately resulting in a desire to drink. In the cold it has also been suggested that there is a blunted thirst response which may affect water intake volumes (Kenefick et al, 2008). Following 30-min exposure to the cold, Kenefick and colleagues reported that the sensation of thirst was attenuated to a serum osmolality threshold of approximately 304 mOsmol·kg -1 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have examined the response to cold exposure without periods of exercise (Kenefick et al, 2008: O'Brien et al, 1998 and have not combined this with a recovery period allowing ad libitum water rehydration to be monitored. Although in this study, the recovery period was at a temperature of approximately 22.2 °C; therefore not causing continual exposure to the cold environment, this situation was felt to occur more readily in a sporting situation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Association of sweat [Na ϩ ] with serum osmolality, serum [Na ϩ ], %⌬PV, hormone responses, and ad libitum drinking and association of serum [electrolytes] with ad libitum drinking were analyzed with Pearson product-moment correlation. The number of subjects in each group (minimum of 6) provided sufficient statistical power (␤ ϭ 0.20) to detect a thirst rating difference equal to two times (1.0) the typical within-subject SD of 0.5, based on intrasubject variablility in thirst ratings determined in a previous study (18). Statistical testing was conducted using SPSS (version 17.0; Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%